Analisis Purchasing Intention Melalui Penggunaan Augmented Reality Di Aplikasi Belanja Online - Hutami, Lusia Tria Hatmanti; Maharani, Bernadetta Diansepti; Indraswari, Nurul Myristica (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim: This study aims to analyze consumers' online purchase intentions by adopting AR technology in online sales applications in Indonesia. The main objective of this study is to analyze the extent of the influence of perceived ease of use, the effect of perceived pleasure, and the influence of personal innovation on attitudes towards AR in online purchasing as a mediating variable with online purchase intention being the dependent variable. Design/Methode/Approach: The research method used in this research is path analysis using the AMOS program before the path analysis goodness of fit test is performed to test the model's fit. The sampling method used is non-probability sampling with the purposive sampling method. The sampling criteria used in this study are consumers who are interested in buying using AR technology or have used AR technology in online shopping applications. Research Finding: People feel that AR technology makes purchasing easier. People who tend to be open to using AR technology are people who have a high level of innovation. This result of the research filled the gap of the use of technology involvement in the marketing area. Theoretical contribution/Originality: Based on these results, The contribution of the research is to bring clarity and development of the technology involved in the marketing field, particularly the use of AR technology. Practitioner/Policy implication: The implications for companies need to make appropriate and fun promotional strategies such as advertising with the aim of building positive attitudes of prospective consumers towards the use of AR in e-commerce media and providing instructions for using AR technology in an interesting way, for example by collaborating with celebrities or celebrity endorsers. Research limitation: This research is limited to shopping applications only. So it is necessary further to investigate the use of AR in other applications.